Deterring or Entertaining? Can the Caning Punishment Execution in Aceh Meet its Objective? (Mazahib, 2020)
This article probes whether the implementation of the caning sentence in Aceh may reach its objective of deterrent effect given the way the execution conducted. From the field observation, the flogging was not much different from entertainment. The mass gathered in one place to watch the execution; they include children, street vendors, researchers, and journalists. There was a stage, VIP seats for guests, loudspeakers, administrative arrangements, and the caning punishment procession. Using a qualitative research approach with an in-depth interview method, it seeks to understand how the community involved in the caning execution was and how the government was designed the sentence as such and why.  It finds that while the government saw the caning law as the implementation of Islamic sharia in Aceh, the people perceived its execution more as entertainment. The government has used the caning sentence execution as a demonstration of power, often for a political gain, because it emphasizes its presence not only as of the guardian of shari’a for Acehnese but also as a devout politician who keeps his political promises. Yet, little of this punishment deterrent effect conveyed to the society due to the way it was staged and executed.Keywords: Qanun Jinayat, Aceh, Caning Punishment, Stage, Entertainment, Deterrent Effect.